Shrinkage quantile regression for panel data with multiple structural breaks. Issue 3 (25th September 2021) - Zhang, Liwen; Zhu, Zhoufan; Feng, Xingdong; He, Yong
Abstract : We consider a shrinkage quantile regression model for high‐dimensional panel data with multiple structural breaks. The structural breaks are assumed to be common across all individuals, but may vary across different quantile levels while sharing an identical location shift effect. We impose an L 1 penalty on the individual effects and an L 1 ‐type fusion penalty to estimate both the slope coefficients and the structural breaks by combining information at multiple quantile levels. The proposed method can detect "partial" changes of the regression coefficients and consistently estimate both the number and dates of the breaks with probability tending to 1. We establish the asymptotic properties of the proposed regression coefficient estimators as well as their post‐selection counterparts, where the dimensionality of the covariates is allowed to diverge. Simulation results demonstrate that the proposed method works well in finite‐sample cases. Using the proposed method, we obtain many interesting results by analyzing a dataset concerning environmental Kuznets curves. Résumé : Les auteurs de ce travail présentent un modèle de régression quantile à rétrécisseur pour données de panel en haute dimension avec des ruptures structurelles multiples. Les ruptures structurelles sont supposées être communes à tous les individus, mais peuvent varier entre différents niveaux de quantiles tout en partageant un même effet de changement de paramètre de position. En imposant aux effets individuels une pénalité de type L 1, en combinant les informations sur plusieurs niveaux de quantiles et en ayant recours à une pénalité de fusion L 1, les auteurs ont pu estimer simultanément les coefficients de pente et les ruptures structurelles. La méthode proposée est capable de détecter les changements "partiels" des coefficients de régression et d'estimer de manière cohérente le nombre et les dates des ruptures avec une probabilité qui tend asymptotiquement vers un. Ils établissent les propriétés asymptotiques des estimateurs de coefficients de régression proposés ainsi que de leurs équivalents post‐sélection lorsque la dimension des covariables peut être divergente. Ensuite, ils présentent des études de simulation montrant que les estimateurs proposés offrent des performances satisfaisantes et obtiennent de nombreux résultats intéressants en analysant un ensemble de données ayant trait à des courbes de Kuznets environnementales.